Sustainable Alternative Syngas Fuel - Ghenai, Chaouki; Inayat, Abrar (IntechOpen, 2019)
The development and use of sustainable and alternative fuels (syngas, biogas, biodiesel, bio-oil, hydrogen) derived from sources other than petroleum is needed due to the limited fossil fuel resources, the need for reduction of atmospheric greenhouse gas emissions, energy security, and to meet the future high energy demand due to population growth. New alternative fuels that can be produced locally and derived from renewable sources will be more sustainable compared to fossil fuels. Alternative and renewable fuels can be produced using different thermochemical and bio-chemical processes. Gasification is a thermochemical process used to produce syngas fuel (mainly hydrogen and carbon dioxide) from renewable (biomass) and conventional (coal) sources. The syngas fuels produced from the gasification process can be used for different applications: power generation (combustion of syngas fuel in gas turbine engines), heating, and transportation (internal combustion engines). This book intends to provide the reader with an overview of the current technologies, methods, and strategies of syngas fuel production, characterization, and application.